Government guarantees and public debt in Croatia - Anto Bajo; Marko Primorac (Financial Theory and Practice, 2011)
Government fi nancial and performance guarantees have been issued in Croatia since 1996, to support funding and ensure favourable borrowing conditions in the fi nancial market for companies in majority state ownership. However, government guarantees have rarely been part of defi ned strategies and goals of public debt and risk management. Despite their steady growth, the structure of active guarantees and their infl uence on Croatian public debt are still unknown. This paper analyses the amount and structure of state guarantees, their maturities and the authority and accountability for their management, and it compares the structure of guarantees in terms of economic sectors. The main objective of the paper is to determine the infl uence of government guarantees on the public debt growth.